Unveiling the future of cardiac care: advances in mechanical circulatory support - Tarcan, Bora (Journal of Mechatronics and Artificial Intelligence in Engineering, 2024)
Congestive heart failure (CHF) is a multifaceted clinical syndrome characterized by the inability of the heart to pump blood effectively, leading to inadequate oxygen and nutrient delivery to the body tissues. Despite advancements in treatment strategies, including guideline-directed medical treatment (GDMT), end-stage CHF remains a significant cause of morbidity and mortality worldwide. Heart transplantation is considered to be the gold standard treatment of end stage CHF but constrained by the lack of organ donors, lengthening waitlists, and the negative side effects of lifelong immunosuppressive medications. Mechanical circulatory support (MCS) has emerged as a pivotal intervention for patients with end-stage CHF, serving as a bridge to recovery, transplantation, or destination therapy. The aim of this narrative review is to highlight the historical development of MCS, to assess the recent status of MCS device technology and discuss current challenges associated with complications of MCS that need to be solved in the future by device development. The history of MCS dates back to pioneering efforts in the 1960s, with significant progress in device development and utilization over decades. MCS devices, including left ventricular assist devices (LVADs), extracorporeal membrane oxygenation (ECMO), and artificial hearts, play a crucial role in providing circulatory support to patients with end-stage CHF. Recent advancements in MCS technology aim to decrease the device size, enhance blood compatibility, reduce thrombo-embolic complications, and prolong device durability and battery life and improve physiological performance of MCS. Continued research and innovation are essential to address these challenges and improve outcomes in patients with end-stage CHF. Artificial intelligence (AI) has emerged as a valuable tool in cardiovascular medicine to facilitate risk prediction, patient selection, and treatment optimization for MCS and heart transplantation. Despite these advancements, challenges persist in MCS device selection, resource allocation, and integration of AI into clinical practice. Continued research and innovation are essential to address these challenges and improve outcomes in patients with advanced heart failure.